Determining the Existence and Strength of Teen Dating Violence Policy: Testing a Comparative State Internal Determinants Model. Issue 5 (March 2022) - Black, Beverly; Ravi, Kristen; Hoefer, Richard
Research demonstrates that Teen Dating Violence (TDV) programs impact TDV knowledge, attitudes, and behaviors, decreasing the odds of TDV victimization and perpetration. Studies indicate that students who do not complete a TDV intervention have significantly higher odds of physical and emotional TDV victimization and emotional TDV perpetration. This study uses multiple logistic regression and multiple linear regression to examine predictors of the presence and the strength of state legislation addressing TDV education and school policies. Results indicate some success in predicting the existence of TDV laws but less support for forecasting the strength of the policies passed. Dominant political party and state median income were found to be potentially important determinants of TDV state school policies. A state's political culture influenced the strength of states' TDV policies. Showing that policy existence and strength are related to different processes is important for advocates to understand. Future research should look at additional variables and explore legislative histories.